The networked school leader : how to improve teaching and student outcomes using learning networks - Brown, Chris (Emerald Publishing Limited, 2020)
As accountability increases while budgets decrease, a growing number of school leaders and policy-makers are turning their attention to Professional Learning Networks (PLNs) as a way of improving education and student outcomes in schools and across school systems. Although PLNs can have real benefits for teachers and students, a number of underpinning conditions need to be in place to ensure these networks have real impact. Key amongst these conditions is effective leadership. The role of school leaders is crucial to ensure that there is meaningful participation by their teachers in network activity and that this participation makes a difference within teachers' 'home' schools. In this timely book Chris Brown addresses the knowledge gap about how school leaders can effectively develop, support, and sustain PLNs within and across schools, drawing on two key case studies from England and Germany. Evidence-based, accessible, and engaging, with key takeaways for practitioners in every chapter, The Networked School Leader is crucial reading for school leaders, system leaders and education researchers working close-to-practice.